2011
DOI: 10.1177/0885066610384192
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Vena Cava Variation Compared to Pulse Contour Analysis as Predictors of Fluid Responsiveness: A Prospective Cohort Study

Abstract: ECHO assessment of the IVC variation during mechanical ventilation may prove to be a useful technique to predict FRes and guide fluid resuscitation in the ICU. The SVV obtained with the Vigileo monitor failed to predict FRes likely due to lack of calibration and the use of a complex algorithm that may be unreliable in patients with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 63 publications
0
52
0
2
Order By: Relevance
“…Following this study there was a revolution in ultrasound technology which facilitated a less invasive approach, and in 2016 most clinicians prefer transthoracic echocardiography rather than the transesophageal approach to assess the IVC. Multiple studies analyzed the IVC in ICU patients under controlled mechanical ventilation [4144]. Together these studies demonstrated that, like static measures of central venous pressure, the absolute size of the IVC was not able to accurately predict the effect of fluid infusion on cardiac output.…”
Section: Mechanical Ventilation Induced Variations In Vena-caval Diammentioning
confidence: 99%
“…Following this study there was a revolution in ultrasound technology which facilitated a less invasive approach, and in 2016 most clinicians prefer transthoracic echocardiography rather than the transesophageal approach to assess the IVC. Multiple studies analyzed the IVC in ICU patients under controlled mechanical ventilation [4144]. Together these studies demonstrated that, like static measures of central venous pressure, the absolute size of the IVC was not able to accurately predict the effect of fluid infusion on cardiac output.…”
Section: Mechanical Ventilation Induced Variations In Vena-caval Diammentioning
confidence: 99%
“…Moreover, if cardiopulmonary function cannot compensate for the increase in preload, fluid loading may compromise microvascular perfusion and oxygen delivery and cause or aggravate peripheral and pulmonary edema [3,4]. Therefore, inappropriate fluid expansion can increase morbidity and mortality [5-7], making it important to accurately assess fluid responsiveness in critically ill patients [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…They found no association between this and the expected hemodynamic response, as measured by CO from transthoracic echocardiography. Feissel et al 77 assessed performance of IVC respiratory variation in a cohort of mechanically ventilated MICU patients; they found that an IVC distensibility index of 12% not only identified volume responders (defined as an increase in CO >15% with 8 mL/kg of colloid) with a positive predictive value and negative predictive value both >92%, but it also correlated highly with CO. Machare-Delgado et al 34 demonstrated that a >12% respiratory variation in IVC was able to identify volume responsiveness (defined as a >10% increase in stroke volume index, the stroke volume divided by body surface area) with a sensitivity of 100% and specificity of 53%. (The investigators did not use airway pressure to gauge the appropriate measurement times for expiration and inspiration, potentially accounting for the low specificity.)…”
Section: Respiratory Variation Of Echocardiographic Parametersmentioning
confidence: 99%